Extracting BIM information for lattice toolpath planning in digital concrete printing with developed dynamo script : a case study - Weng, Yiwei (2021)
In this paper, a novel method for printing path design in the three-dimensional (3D) concrete printing process (3DCP) has been developed and applied to a large-scale construction process. Despite the large number of research works in digital concrete printing over the last decade, few studies have explored the method of automatic printing path design, specifically designing the printing path by directly extracting building information modeling (BIM) information from the BIM platform in 3DCP. To obtain BIM information and automatically design the printing path, a script package was developed using a single scripting environment called Dynamo, a Revit plug-in. The proposed method was evaluated using the results of simulation and real-time printing. Compared with the conventional method, the simulation results show that the proposed approach can reduce data loss from a 3D BIM model to printing path generation. The real-time printing test implies that the proposed approach is perfectly suitable for integrating BIM with 3DCP.